CFA-7: an interpenetrated metal–organic framework of the MFU-4 family1. Issue 29 (7th August 2015) - Schmieder, Phillip; Grzywa, Maciej; Denysenko, Dmytro; Hambach, Manuel; Volkmer, Dirk
<x xml:space="preserve">Abstract</x> Structural characterization of a novel interpenetrated bistriazolate-based MOF followed by postsynthetic replacement of Zn2+ by M2+ ions (M = Co, Ni, Cu) represents a versatile approach towards redox-active MOFs.